Levels of Family Intervention - Salazar de la Cruz, Miriam (2013)
We face different health problems in primary care, and they have variable impact in both individuals and their families. Also, some foreseeable circumstances in the lives of the individual and of his/her family are required in order to mitigate the impact of a critical event on family development. There are five levels for family interventions, which are based upon the degree of familial involvement, assuming this would lead to better understanding the individual's problems, and this may also lead to a greater likelihood for solving them. It is also important to know when a family problem may require referral to a next level for intervention. In our country, we need to have adequate services, we have to train professionals with specific abilities in working with families and we also have to reinforce regulations that may facilitate advances in this field.